Aspergillus fumigatus Photobiology Illuminates the Marked Heterogeneity between Isolates - Kevin K. Fuller (mBio, 2016)
The given strain of Aspergillus fumigatus under study varies across laboratories, ranging from a few widely used “standards,” e.g., Af293 or CEA10, to locally acquired isolates that may be unique to one investigator. Since experiments concerning physiology or gene function are seldom replicated by others, i.e., in a different A. fumigatus background, the extent to which behavioral heterogeneity exists within the species is poorly understood. As a proxy for assessing such intraspecies variability, we analyzed the light response of 15 A. fumigatus isolates and observed striking quantitative and qualitative heterogeneity among them. The majority of the isolates fell into one of two seemingly mutually exclusive groups: (i) “photopigmenters” that robustly accumulate hyphal melanin in the light and (ii) “photoconidiators” that induce sporulation in the light. These two distinct responses were both governed by the same upstream blue light receptor, LreA, indicating that a specific protein’s contribution can vary in a strain-dependent manner. Indeed, while LreA played no apparent role in regulating cell wall homeostasis in strain Af293, it was essential in that regard in strain CEA10. The manifest heterogeneity in the photoresponses led us to compare the virulence levels of selected isolates in a murine model; remarkably, the virulence did vary greatly, although not in a manner that correlated with their overt light response. Taken together, these data highlight the extent to which isolates of A. fumigatus can vary, with respect to both broad physiological characteristics (e.g., virulence and photoresponse) and specific protein functionality (e.g., LreA-dependent phenotypes).